PEMAHAMAN MAHASISWA PROGRAM STUDI PENDIDIKAN JASMANI KESEHATAN DAN REKREASI FIK UNY ANGKATAN 2010 TERHADAP PERATURAN PERMAINAN BOLABASKET - Triani Hastuti (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2011)
AbstractThis study aims to determine the student’s level of understanding Physical Education Health and Recreation Study Program (PJKR) FIK 2010 UNY Force basketball game against the regulations. This study is a quantitative descriptive study. The population in this study was students PJKR Force in 2010 which totaled 358 students. Sampling techniques using proportional random sampling a total of 90 students consisting of six classes of 15 students per class is taken. Data collection technique is using questionnaires. Test the validity of using the product moment with 30 original items and items that fall 5 points are valid statements is 25 points. Reliability of the instrument is using the formula cronbach Alpha, Alpha reliability coefficient (R11) the aggregate of 0.753. Data analysis technique is using percentages. Based on the research results can be concluded that students’ understanding PJKR 2010 FIK UNY force said to be good as much as 38.90%. In detail the following 28 students (31.10%) level of understanding of the regulation basketball game is in very good category, 35 students (38.90%) level of understanding of the regulation basketball game is in good category, 22 students (24.40%) level of understanding of the regulation basketball game is in pretty good category, 5 students (6%) level of understanding of the regulation basketball game in the category of poor.Key words: comprehension, students, regulation basketball game.AbstrakPenelitian ini bertujuan untuk mengetahui tingkat pemahaman mahasiswa Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi (Prodi PJKR) FIK UNY Angkatan 2010 terhadap peraturan permainan bolabasket. Penelitian ini merupakan penelitian deskriptif kuantitatif. Populasi dalam penelitian ini adalah mahasiswa Prodi PJKR Angkatan 2010 yang berjumlah 358 mahasiswa. Teknik pengambilan sampel menggunakan proportional random sampling sejumlah 90 mahasiswa yang terdiri dari 6 kelas setiap kelas diambil 15 mahasiswa. Teknik pengumpulan data menggunakan kuesioner. Uji validitas menggunakan product moment dengan butir semula 30 dan gugur 5 butir sehingga butir pernyataan yang sahih adalah 25 butir. Reliabilitas instrumen menggunakan rumus Alpha cranbach, diperoleh koefisien reliabilitas Alpha (r11) keseluruhan sebesar 0,753. Teknik analisis data menggunakan persentase. Berdasarkan hasil penelitian dapat disimpulkan bahwa pemahaman mahasiswa PJKR FIK UNY angkatan 2010 dikatakan baik sebanyak 38,90%. Secara rinci sebagai berikut 28 mahasiswa (31,10%) tingkat pemahaman terhadap peraturan permainan bolabasket berada pada kategori sangat baik, 35 mahasiswa (38,90%) tingkat pemahaman terhadap peraturan permainan bolabasket berada pada kategori baik, 22 mahasiswa (24,40%) tingkat pemahaman terhadap peraturan permainan bolabasket berada pada kategori cukup baik, 5 mahasiswa (6%) tingkat pemahaman terhadap peraturan permainan bolabasket berada pada kategori kurang baik.Kata kunci: pemahaman, mahasiswa prodi PJKR, peraturan permainan bolabasket.